Nutritional status of children under 2 years of age in the municipality of Mossoró, state of Rio Grande do Norte (RN) (Research, Society and Development, 2024)
This study aimed to evaluate the nutritional status of children under two years of age in the municipality of Mossoró-RN, using data provided by the Food and Nutrition Surveillance System (SISVAN). The analysis revealed an increase in the number of children assessed, with a worrying trend of overweight and obesity, especially in 2022 and 2023, and a reduction in appropriate height for age. It was observed that, although most children presented a eutrophic state in body mass index (BMI), the prevalence of overweight and obesity is on the rise, reflecting a significant public health problem. The research highlights the importance of interventions in Primary Health Care and the promotion of healthy eating habits from childhood, as well as the need for effective public policies to address the nutritional challenges identified.